Molecular tools with statistical analysis on trichloroethylene remediation effectiveness. (October 2020) - Liu, Pao-Wen Grace; Wu, Yi-Ju; Whang, Liang-Ming; Lin, Tsair-Fuh; Hung, Wei-Nung; Cho, Kun-Ching
Abstract: Enhanced monitored natural attenuation was conducted with molasses injections to an in situ trichloroethylene (TCE)-contaminated groundwater site. Three pilot-scale wells were conducted for monitoring and substrate injections. At most 97.0% of the TCE was effectively degraded after about 600 days. TCE detected in the injection wells attained Tier 2 Groundwater Regulation in Taiwan for non-drinking water sources. The reaction rates of Cl–VOCs in one of the injection wells explained the mechanism how these dechlorinating species transferred TCE to cis-DCE and VC in anaerobic conditions. The magnitude of the 1st order kinetic growth rates of Dehalococcoides (Dhc) were consistent with the associated TCE degradability. The qPCR and T-RFLP results concluded existence of crucial dechlorinating species including Dhc, which performed critical level of 10 6 copy L −1 to trigger the TCE degradation. The detected t ceA and vcrA ranging from 2.07 × 10 3 to 6.57 × 10 5 copy L −1 confirmed the pathway of TCE degradation. The two injection wells with the optimal TCE degradation showed increases of bacterial diversity estimated by the Shannon Index. The Shannon index explained the superiority of an increased bacterial diversity. The nonmetric multidimensional scaling results suggested that the bacterial dynamic was affected by the TCE degradation stages. The bacterial community structures were analogous when TCE was well degraded. Highlights: The molecular results provided evidence of existence of crucial dechlorinating species including Dehalococcoides spp. Dehalococcoides spp. With the critical abundance of 10 6 copy L −1 was critical for TCE degradation. Detections of tceA (as high as 10 7 copy L −1 ) and vcrA confirmed the pathway of TCE degradation. The optimal TCE degradation was observed with increases of bacterial diversity estimated by the Shannon Index. Nonmetric multidimensional scaling result indicated the bacterial community dynamic depended on the TCE degradation stages.